1989
DOI: 10.1161/01.res.65.2.446
|View full text |Cite
|
Sign up to set email alerts
|

Shortening velocity and myosin and myofibrillar ATPase activity related to myosin isoenzyme composition during postnatal development in rat myocardium.

Abstract: The relation between functional properties of the contractile apparatus, such as shortening velocity and ATPase activity, and myosin isoenzyme composition was studied in ventricular myocardium of adult (60-90-day-old) rats and of newborn (3-day-old) and young (10- and 20-day-old) rats. In adult animals, variations of isomyosin pattern were produced by reducing food intake and by changing the thyroid state. Hyperthyroidism was induced with triiodothyronine daily injection for 15 days; hypothyroidism was induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 49 publications
1
37
0
Order By: Relevance
“…Hoh et al 16 and other investigators 22,23 have reported that the ATPase activity of myosin V3 is lower than that of myosin V1, and that the rate of cross-bridge cycling measured by myocardial shortening velocity is correlated with increases and/or decreases in myosin ATPase activity. Therefore, oscillations of energy metabolism may be less obvious in hearts with V3 dominance in myosin isozyme distribution.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Hoh et al 16 and other investigators 22,23 have reported that the ATPase activity of myosin V3 is lower than that of myosin V1, and that the rate of cross-bridge cycling measured by myocardial shortening velocity is correlated with increases and/or decreases in myosin ATPase activity. Therefore, oscillations of energy metabolism may be less obvious in hearts with V3 dominance in myosin isozyme distribution.…”
Section: Discussionmentioning
confidence: 95%
“…Cappelli et al have reported that the myosin ATPase activity, shortening velocity, and relative composition of V1 myosin are much higher in hyperthyroid rats than in normal rats, although the myosin isozyme distributions in both groups show myosin V1 dominance. 22 The larger magnitude of fluctuations in energy metabolites in the hyperthyroid rat hearts may be attributable to the increased myosin ATPase of these preparations.…”
Section: Discussionmentioning
confidence: 98%
“…However, the fact that lead binds to sulfhydryl (SH) groups suggests that the metal could affect contractile proteins (27,28). The activity of myosin, for example, is reduced by Hg, which also binds to SH groups (21).…”
Section: Discussionmentioning
confidence: 99%
“…To determine if lead acetate is capable of affecting myosin ATPase activity, the effects of this metal were assayed as described previously (20,21). Briefly, myosin was prepared from minced and homogenized right ventricles (N = 7), extracted briefly with KCl phosphate buffer (0.3 M KCl, 0.2 M phosphate buffer, pH 6.5) (22).…”
Section: Myosin Atpase Activitymentioning
confidence: 99%
“…Myosin ATPase activity was assayed (23,24) by measuring Pi liberation from 1 mM ATP in the presence of 50 mM HEPES, pH 7, 0.6 M KCl, 5 mM CaCl 2 or 10 mM EGTA in a final volume of 200 µl. In the presence of this high ionic strength with no addition of Mg 2+ to the incubation medium, only myosin activity is measured and there is no significant activity of Mg 2+ -ATPase, which is an actin-contaminated myosin.…”
Section: Assay Of Myosin Atpase Activitymentioning
confidence: 99%